THE REFLECTION OF THE TRAUMA OF THE MACEDONIAN PEOPLE IN THE NOVELS OF GJORGJI ABADJIEV AND TASHKO GEORGIEVSKI (Philological Studies, 2024)
World history is inscribed with wars and revolutions that history and politics perceive through facts. Psychiatry deals with the traumatic consequences to people, which often find a place in literature. Numerous works have been written by direct participants, witnesses of those events, as well as their descendants. Macedonian history abounds with historical events that have left deep-rooted traumas to the Macedonian people. During the 19th century, when states and nations were formed, numerous rebellions and uprisings organized by the Macedonian people who fought for freedom from five centuries of slavery and for the right to self-determination. However, the great powers had a territorial interest in Macedonia, which is why they did not take into account the democratic right of the Macedonian people, and they turned a deaf ear to their appeals for help. Therefore, in 1903 in Thessaloniki, a group of young revolutionaries - the Thessaloniki Assassins carried out an attack through which they wanted to draw attention to the Macedonian issue. Gjorgji Abadjiev writes about the psychological consequences to one of the survivors of this historical act in the novel Pustina. The fate of the Macedonian people had been decided in a most undemocratic manner in 1913, with the Bucharest Agreement, which had divided the territory of Macedonia, and with it, the Macedonian people had been disintegrated. Tashko Georgievski writes about this political andhistorical event, which left a trauma on the Macedonian people, individually and collectively, and which is reflected to this day, in his nine novels titled Black Seed.